Troubling a star - L'Engle, Madeleine (Laurel-leaf books, 1995)
As she tries to stay alive after being left on an iceberg in the Antarctic, sixteen-year-old Vicky recalls the series of events that brought her to the bottom of the world and involved her in a dangerous mystery.